Resilience of Adolescent Victims of Sexual Violence in View of Family Support and Gender - Bidayah, Afifah; Karneli, Yeni (Bisma The Journal of Counseling, 2024)
The increase in cases of sexual violence occurring among teenagers raises concerns about the psychological impact they experience. To face the impact, teenagers need resilience, which is how they can respond to the problems they experience more positively, endure difficult conditions, and bounce back. This research aims to analyze the resilience levels of adolescent victims of sexual violence in terms of family support and gender, as well as the differences. The research uses a quantitative approach with descriptive comparative methods and is deepened with interviews. The findings of the research show that 1) overall, the resilience level of adolescent victims of sexual violence is good, meaning they can endure despite experiencing trauma, 2) there is a significant difference in the resilience of adolescent victims of sexual violence when viewed from family support; the better the family support, the better the resilience, 3) there is a significant difference in the resilience of adolescent victims of sexual violence when viewed from gender; males have better resilience compared to females, 4) there is no interaction between family support and gender in explaining the resilience of adolescent victims of sexual violence.